Renda básica universal: liberdade real para todas? Críticas feministas ao libertarismo real de Philippe Van Parijs - Lorena Fonseca Silva (2019)
In this dissertation, I propose a debate on the adequacy of Philippe Van Parijs's proposal of unconditional basic income and real freedom in relation to the objective of minimizing gender inequalities. For such, I submit aspects of the author's theory to criticisms of feminist biases in three fronts. In the first one, I present and analyze feminist authors' debate about the basic income proposal and its capacity for fulfilling its freedom project. In the second, I bring the intersectional bias to stress the impact of basic income for women excluded from hegemonic feminism. Lastly, in the third, I analyze the basic income proposal in opposition to the capabilities perspective. The present research is guided by the following problem: "To what extent is Van Parijs's basic income proposal an alternative to women's freedom and independence demands?" My general objective is to analyze to what extent the basic income can attend to the feminist agenda, contributing to gender equality. My specific objectives are: a) to present Van Parijs theory regarding real freedom and the proposal of basic income; b) to present and analyze feminist defenses and critiques about the author's proposals; c) to present and to dialogue intersectional feminism with basic income proposal and, finally, d) to present and to counterpose the capabilities approach as an alternative to women's real freedom proposal. The conclusions of the research were as follows: First, in presenting and analyzing feminist defenses and critiques on the potential of basic income for gender equality, I have concluded that, in the synthesis of the arguments in terms of earnings and losses for the family, for the market and for the person, the arguments in favor of basic income prevailed as a measure for gender equality. Second, in analyzing Van Parijs's theory and its potential for correcting gender imbalances, encompassing security, self-ownership and lexmin opportunities, I have concluded that, even though there is an overlap in the benefits of basic income, the model, per se, is not a sufficient measure to meet all the conditions of women's real freedom. Thirdly, in discussing the basic income proposal with intersectional feminism, analyzing it in terms of life options and income for women suffering from complex inequalities, I have concluded that the basic income proposed by Van Parijs does not meet all the challenges proposed by intersectional feminism. Fourth, by presenting and opposing the capabilities approach as an alternative to women's real freedom proposition, I have concluded that Van Parijs' real freedom and the basic income proposition are no longer adherent to feminist standards than the theory of capabilities. Therefore, in response to all of the above, the answer to the research problem is "partially", since basic income, despite being an important proposition for gender equality, is an action that demands complementary measures to guarantee equality and freedom.